A lipopolysaccharide-free outer membrane vesicle vaccine protects against Acinetobacter baumannii infection. Issue 4 (22nd January 2020) - Pulido, Marina R.; García-Quintanilla, Meritxell; Pachón, Jerónimo; McConnell, Michael J.
Highlights: LPS-deficient A. baumannii produces outer membrane vesicles (OMVs). OMVs derived from LPS-free A. baumannii are highly immunogenic. Immunization with OMVs from LPS-free A. baumannii provides protective immunity. Abstract: Outer membrane vesicles (OMVs) were isolated from an Acinetobacter strain deficient in lipopolysaccharide (LPS) due to a mutation in lpxD (IB010). Two immunizations with 10 µg of IB010 OMVs elicited total IgG, IgM, IgG1 and IgG2c titers similar to those observed after immunization with OMVs derived from the parental strain (ATCC 19606), and IB010 OMVs plus purified LPS. Immunization with IB010 OMVs resulted in significantly reduced post-infection spleen bacterial loads and serum IL-1β and IL-6 levels compared to control mice in a disseminated sepsis model. Mice immunized with 10 µg IB010 OMVs demonstrated significant, but partial, protection (75%) against infection, whereas mice immunized with ATCC 19606 OMVs or IB010 OMVs plus purified LPS were completely protected. Immunization of mice with 100 µg of IB010 OMVs completely protected mice from infection. This study demonstrates that LPS deficient A. baumannii produces OMVs, and that immunization with these OMVs elicits protective immunity against infection.